Microcystin-LR induces angiodysplasia and vascular dysfunction through promoting cell apoptosis by the mitochondrial signaling pathway. (March 2019) - Wang, Qilong; Liu, Yuanli; Guo, Jingsong; Lin, Song; Wang, Yeqi; Yin, Tieying; Gregersen, Hans; Hu, Tingzhang; Wang, Guixue
Abstract: The harmful algal blooms are becoming increasingly problematic in the regions that drinking water production depends on surface waters. With a global occurrence, microcystins are toxic peptides produced by multiple cyanobacterial genera in the harmful algal blooms. In this study, we examined the effects of microcystin-LR (MC-LR), a representative toxin of the microcystin family, on vascular development in zebrafish and the apoptosis of human umbilical vein endothelial cells (HUVECs). In zebrafish larvae, MC-LR induced angiodysplasia, damaged vascular structures and reduced lumen size at 0.1 μM and 1 μM, leading to the decrease of the blood flow area in the blood vessels and brain hemorrhage, which showed that MC-LR could dose-dependently inhibit vascular development and cause vascular dysfunction. In MC-LR treated HUVECs, the proportion of early apoptosis and late apoptosis cells increased in a concentration-dependent manner. Different concentrations of MC-LR could also activate caspase 3/9 in HUVECs, increase the level of mitochondrial ROS and reduce mitochondrial membrane potential. Additionally, MC-LR could promote the expression of p53 and inhibit the expression of PCNA. The findings showed that MC-LR could promote apoptosis of HUVECs through the mitochondrial signaling pathway. Combined with these results, MC-LR may promote vascular endothelial cell apoptosis through mitochondrial signaling pathway, leading to angiodysplasia and vascular dysfunction. Graphical abstract: Image 1 Highlights: Microcystin-LR induces angiodysplasia and vascular dysfunction. Microcystin-LR damages vascular structures and reduces lumen size. Microcystin-LR reduces vascular patency. Microcystin-LR causes brain hemorrhage. Microcystin-LR promotes cell apoptosis by the mitochondrial signaling pathway.